2019
DOI: 10.1002/jsid.752
|View full text |Cite
|
Sign up to set email alerts
|

A study on differences in human perception between a real and an AR scene viewed in an OST‐HMD

Abstract: With the recent growth in the development of augmented reality (AR) technologies, it is becoming important to study human perception of AR scenes. In order to detect whether users will suffer more from visual and operator fatigue when watching virtual objects through optical see‐through head‐mounted displays (OST‐HMDs), compared with watching real objects in the real world, we propose a comparative experiment including a virtual magic cube task and a real magic cube task. The scores of the subjective questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At the same time, the stereo sense gradually decreases with the increase of the angular parallax amplitude. The reason is that the larger parallax can still observe the depth, but the stereo sense will not increase further [9],which shows that the sensitivity of the human eye to the depth difference will increase first and then gradually decrease with the increase of parallax [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the stereo sense gradually decreases with the increase of the angular parallax amplitude. The reason is that the larger parallax can still observe the depth, but the stereo sense will not increase further [9],which shows that the sensitivity of the human eye to the depth difference will increase first and then gradually decrease with the increase of parallax [5].…”
Section: Resultsmentioning
confidence: 99%
“…used stereograms containing random positioning circles to study how different parallax amplitude cause changes in depth perception and realism. The results show that with the increase of parallax amplitude, the perception depth increases, and the sense of reality increases first and then decreases, that is, a smaller angular parallax within 30 arc min is needed to enhance the sense of reality [5].…”
Section: Some Scholars Have Conducted Relevant Research On How Angula...mentioning
confidence: 93%
“…Performing visual tasks on OHMDs for any duration induces visual fatigue and VIMS. Gao et al [33] indicated that the CFF value decreases as visual task duration increases with optical see-through head-mounted displays (OST-HMDs). Kaufeld et al [7] detected VIMS symptoms while participants performed both static and dynamic AR tasks while participants wore the OHMD.…”
Section: Of 15mentioning
confidence: 99%
“…Previous studies have used HRV indicators to examine the physical stress associated with stereoscopic displays [40,44,49,51,52]. For instance, Tumler et al [16] objectively evaluated user strain during picking tasks in an industrial warehouse while using either an AR system or a simple paper list instruction, with measurements based on HRV.…”
Section: Introductionmentioning
confidence: 99%
“…Their evaluation, however, was limited to research using HMDs for virtual reality. Gao et al [51] assessed visual fatigue when viewing virtual magic cube tasks through optical see-through HMDs (OST-HMDs) compared to viewing real objects in the real world. They found that participants were more likely to experience discomfort when viewing virtual objects presented by OST-HMDs.…”
Section: Introductionmentioning
confidence: 99%